PERAN MATA PELAJARAN PENJASORKES PADA KARAKTER PESERTA DIDIK KELAS VIII DI SMPN 10 PONTIANAK - Wulandari, Indah; Hidasari, Fitriana Puspa; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem of this research is how great the role of physical education, sports and health subject toward students character to the eighth grade students of SMPN 10 Pontianak. The aim of this research is to find out how great the role of physical education, sports and health subject toward students character to the eighth grade students of SMPN 10 Pontianak. This research method used survey techniques which is questionnaire with quantitative research design. The population of this research was eighth grade students of SMPN 10 Pontianak. The sampling technique of this research used Simple Random Sampling with the total of sample was 47 students. Thereafter instrument testing was done to measure the validation used product moment correlation technique which is done with MS. Excel. The analysis technique in this research used quantitative descriptive statistics calculation with percentages. Based on the research which has been conducted, the result showed that the role of physical education, sports and health subject toward students’ character amount 8,51% of 4 respondents represented that physical education, sports and health subject highly influence of students’ character building, 38,30% of 18 respondents represented that the role of physical education, sports and health subject quite influence, 34,04% of 16 respondents represented that the role of physical education, sports and health subject less influence, and 19,15% of 9 respondents represented that the role of physical education, sports and health subject highly not influence. Keywords: Character, Physical Education